POWER THROUGH THE USE OF PERSONAL PRONOUNS IN E-MAIL INTERACTIONS OF PEDOPHIL: CRITICAL DISCOURSE ANALYSIS - Antok Risaldi (Universitas Negeri Makassar, 2023)
This study examines the choice of personal pronouns made by pedophiles in interactions in e-mail. The main focus of this study is to determine who is downloaded by the two pedophiles, namely JON and ZEE when using personal pronouns and compare the use by the two pedophiles. The data of this research is in the form of conversations involving both pedophiles in interactions in electronic mail. Data collection is done through non-participating observation techniques which are suitable for observing activities that are not possible to be involved in. The data obtained from observations in the form of screenshots of the conversations of the two pedophiles in the telegram group were then stored in the data folder. The analysis of the use of personal pronouns in this study uses Fairclough's critical discourse analysis (CDA) dimension model in the form of description, interpretation, and explanation. The results showed that the use of personal pronouns in the interaction of the two pedophiles in electronic mail had a significant difference. The findings of this study indicate that the perpetrators of ZEE crimes use the words of the first and third people which are the most dominant compared to the perpetrators of JON crimes. The dominance of the use of first person pronouns by criminals as evidenced by the use of the words I, I, and we. For the use of the second person pronouns used in the form of you, while the use of the third person pronouns in the form of he and they. The conclusion of this study is that using personal pronouns in pedophile interactions in electronic mail has power in various forms